2022
DOI: 10.1001/jamacardio.2022.1437
|View full text |Cite
|
Sign up to set email alerts
|

External Support for Saphenous Vein Grafts in Coronary Artery Bypass Surgery

Abstract: and subsequent saphenous vein graft failure may have significant adverse clinical effects in patients undergoing coronary artery bypass surgery. External support of saphenous vein grafts has the potential to prevent vein graft dilation and hence slow the rate of intimal hyperplasia and increase long-term vein patency.OBJECTIVE To determine efficacy, as measured by intimal hyperplasia, and safety of an external saphenous vein graft support device in patients undergoing a coronary bypass graft procedure. DESIGN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…We further analysed the different SVG territories, and the results showed that the graft failure rates in the right territory were higher in the external stented group compared to the non-stented group (RR: 1.73, 95% CI: 1.07 to 2.80, p = 0.02, I 2 = 8%, Figure 3B). 17,19 However, in the left territory, the difference did not reach statistical significance in two groups (RR: 0.85, 95% CI: 0.58 to 1.25, p = 0.41, I 2 = 19%, Figure 3A). The heterogeneity was not obvious, and sensitivity analyses were not performed to detect the source of this statistical heterogeneity.…”
Section: Efficacy Outcomementioning
confidence: 89%
See 3 more Smart Citations
“…We further analysed the different SVG territories, and the results showed that the graft failure rates in the right territory were higher in the external stented group compared to the non-stented group (RR: 1.73, 95% CI: 1.07 to 2.80, p = 0.02, I 2 = 8%, Figure 3B). 17,19 However, in the left territory, the difference did not reach statistical significance in two groups (RR: 0.85, 95% CI: 0.58 to 1.25, p = 0.41, I 2 = 19%, Figure 3A). The heterogeneity was not obvious, and sensitivity analyses were not performed to detect the source of this statistical heterogeneity.…”
Section: Efficacy Outcomementioning
confidence: 89%
“…Two studies 17,19 reported SVG failure rates (≥ 50% stenosis); the results showed that the external support device for SVGs did not increase the overall SVG failure rate compared with non-stented group (RR: 1.14, 95% CI: 0.85 to 1.52, p = 0.38, I 2 = 0%, Figure 2D). The heterogeneity was low based on the heterogeneity test (I 2 = 0%).…”
Section: Efficacy Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Patients who have three-diseased vessel, with left ventricular ejection fractions (LVEF) > 3%, or severe disease in the left main corona artery are candidates for the CABG operation. Compared to medicinal therapy or percutaneous procedures like angioplasty or stents, surgical revascularization (CABG) has lower longterm morbidity and mortality rates, (Goldstein et al, 2022). The degree of issues linked to CABG surgery can shed light on patients' and nurses' opinions regarding that leg and chest wounds, drugs, and complications were the most critical learning needs for the patients relative to other domains.…”
Section: Introductionmentioning
confidence: 99%